Penerapan Eletronic Traffic Law Eforcement (ETLE) terhadap Pelanggaran Lalu Lintas di kota Tanjung Pinang - Nabila Rosiano; Susi Afriani; Leni Karlina (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
This research examines the implementation of Electronic Traffic Law Enforcement (ETLE) as a technological innovation in traffic law enforcement in Tanjungpinang City. The main objectives of ETLE are to reduce traffic violations, eliminate extortion practices, and improve road safety. The method used in this research is normative juridical, with an approach to secondary data in the form of laws and regulations related to traffic and road transportation. The results showed that ETLE played an effective role in suppressing traffic violations, although there were still obstacles, such as lack of facilities and infrastructure, low public understanding, and technical obstacles in implementation. Factors driving the success of ETLE include legal substance, law enforcement, supporting facilities, community legal culture, and infrastructure readiness. To increase effectiveness, it is recommended that the socialization of ETLE procedures be improved, legal supervision be strengthened, and the scope of ETLE devices be expanded. This is expected to optimize traffic law enforcement and create a safer traffic environment in Tanjungpinang.